Brain structural changes in girls with idiopathic central precocious puberty: a voxel-based morphometry and surface-based morphometry analysis - Zhang, Yun; Tian, Lu; Wang, Xiaojian (Frontiers in Endocrinology, 2025)
ObjectivesThis study aimed to investigate brain structural alterations in girls with idiopathic central precocious puberty (ICPP) using voxel-based morphometry (VBM) and surface-based morphometry (SBM), and to explore associations between these changes and clinical indicators to elucidate the impact of ICPP on brain structure and uncover its underlying mechanisms.Materials and methodsFifty-two girls aged 6–8 years with ICPP and 50 age-matched non-ICPP girls underwent 3.0 T MRI T1-weighted imaging. Structural data were analyzed using SPM12 and CAT12. A two-sample t-test assessed differences in global and regional brain volumes and cortical thickness. Correlation analyses explored relationships between structural alterations and clinical indicators.Results(1) The ICPP group showed increased total intracranial volume, white matter volume, and cerebrospinal fluid volume, but decreased gray matter volume (p < 0.05). (2) VBM revealed reduced gray matter volume in the right precentral gyrus, bilateral amygdala, bilateral inferior temporal gyrus, and bilateral putamen (FDR-corrected, p < 0.05). (3) SBM showed cortical thinning in the right precentral gyrus (FDR-corrected, p < 0.05). (4) Gray matter volume in the inferior temporal gyrus and right precentral gyrus, and cortical thickness in the right precentral gyrus, were negatively correlated with peak LH levels (FDR-corrected, p < 0.05).ConclusionsVBM and SBM effectively identify brain structural changes in ICPP girls, particularly in regions related to motor control, emotion, and cognition. These alterations, linked to hormonal levels, may serve as imaging biomarkers and offer insights into the neurobiological impact of ICPP.